IMPLEMENTASI GAME EDUKATIF BERBASIS QUIZIZZ UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Muhammad Hasani Zuhri; Suadi (As-Sulthan Journal of Education, 2026)
This study aims to describe the implementation of Quizizz-based educational games in Akidah Akhlak learning, analyze students' learning interest after the application of Quizizz media, and identify the supporting and inhibiting factors. This research uses a qualitative approach with a descriptive type. The research location is at MA YTI Nguling, Pasuruan, involving the Akidah Akhlak teacher and 11th-grade students (14 students). Data collection techniques include participant observation, in-depth interviews, and documentation study. Data analysis was performed through data reduction, data display, and conclusion drawing/verification. The validity of the data was ensured through prolonged engagement, source and method triangulation, and member checking. The findings reveal that: (1) The implementation of Quizizz was carried out through three stages: planning, execution, and evaluation; (2) Students' learning interest significantly increased across all four indicators: feelings of enjoyment, attention and concentration, activeness and engagement, and interest in continuous learning; (3) Supporting factors include device availability, student enthusiasm, teacher support, and Quizizz features; while inhibiting factors include device limitations, signal interference, and initial student distraction. This research contributes to the modification of digital media implementation theory and formulates the principle of